Pancreatic exocrine and endocrine function after pancreatectomy for persistent hyperinsulinaemic hypoglycaemia of infancy. Issue 5 (1st November 1998) - Cade, A; Walters, M; Puntis, J W L; Arthur, R J; Stringer, M D
Abstract : AIM: To evaluate long term detailed pancreatic endocrine and exocrine function in children with persistent hyperinsulinaemic hypoglycaemia of infancy (PHHI) after 85–95% pancreatectomy. METHODS: Six children with PHHI between 0.9 and 12.7 years after pancreatic resection underwent clinical and investigative follow up at 1.0 to 14.9 years of age. One child with PHHI who had not had pancreatectomy was also assessed. Standard endocrine assessment, pancreatic magnetic resonance imaging (MRI), and detailed direct and indirect tests of exocrine pancreatic function were performed. RESULTS: Pancreozymin-secretin stimulation test results were normal in only one child, borderline in two, and deficient in four, one of whom requires daily pancreatic enzyme supplements. Pancreolauryl tests performed in three children were borderline in two and abnormal in the other. Only one child had low faecal chymotrypsin values. One child developed insulin dependent diabetes at 9 years and two children at 1.0 and 13.3 years require diazoxide to maintain normoglycaemia. MRI showed no major regrowth of the pancreatic remnant after resection (n = 5). CONCLUSIONS: Clinical evidence of endocrine or exocrine dysfunction has developed in only two patients to date, but detailed pancreatic function testing suggests subclinical deficiency in all but one of our patients with PHHI. Although 95% pancreatectomy results in postoperative control of blood glucose, subclinical pancreatic insufficiency is present on long term follow up and development of diabetes mellitus and exocrine failure remain ongoing risks.